Economic tools for realization of methane production project on Kuzbass coal deposits; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Sharf I. V. Irina Valerievna; Sokolova М.; Kochetkova O. P. Olga Petrovna; Dmitrieva N. (Petroleum Engineering Economics and Mining Law, 2016)
Title screen